2013
DOI: 10.1007/978-3-642-37437-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Can Gamification Increase Consumer Engagement? A Qualitative Approach on a Green Case

Abstract: The present study aims to identify the potential benefits deriving from the introduction of gamification elements in the consumer shopping process, in order to engage consumers in a more ecologically conscious behavior. Interviews with lead consumers show that the gamification of the shopping process results in increment of the stated intention to participate in the shopping process as well as an increment in the stated intention to purchase and an increase in the price premium consumers are willing to pay for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Organizations have used gamification to encourage targets of influence to complete tasks that may be viewed as boring, unpleasant, or unnecessary by making the tasks seem more rewarding and fun. For example, gamification has been used for facilitating workplace training [ 31 ] and cultivating consumer engagement [ 32 ]. “Serious games” have been receiving attention particularly in the domain of health [ 33 , 34 ], where the games have been used for a variety of interventions, including increasing physical activity [ 35 , 36 ], slowing cognitive decline [ 37 ], improving driving skills [ 38 ], and educating on self-management of health conditions [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organizations have used gamification to encourage targets of influence to complete tasks that may be viewed as boring, unpleasant, or unnecessary by making the tasks seem more rewarding and fun. For example, gamification has been used for facilitating workplace training [ 31 ] and cultivating consumer engagement [ 32 ]. “Serious games” have been receiving attention particularly in the domain of health [ 33 , 34 ], where the games have been used for a variety of interventions, including increasing physical activity [ 35 , 36 ], slowing cognitive decline [ 37 ], improving driving skills [ 38 ], and educating on self-management of health conditions [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis is based on the basic competence of gamification, namely that the use of game mechanisms and game elements can direct human behaviour in a desired direction [6,42]. Gamification motivates people to show a desired behaviour [12]. For example, Murray and Bellman [43] report a positive effect of gamification on purchasing behaviour, and Lounis, Neratzouli, and Pramatari [12] have shown that gamification can increase the willingness to pay for sustainable products.…”
Section: Methodsmentioning
confidence: 99%
“…Gamification motivates people to show a desired behaviour [12]. For example, Murray and Bellman [43] report a positive effect of gamification on purchasing behaviour, and Lounis, Neratzouli, and Pramatari [12] have shown that gamification can increase the willingness to pay for sustainable products. Siemens et al [44] also concluded that gamification has a positive effect on consumer attitudes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The way to revive long-term behaviour that is intended to be stimulated in the short term could be addressed by introducing a process improvement mechanism and incentive tools that support psychological benefits in parallel to others in the form of external rewards [72]. In another sense, some authors speak of the "pro-environmental consciousness," which is fixed to broader personal values and shaped by personality traits, as well as by other social and cultural factors [73].…”
Section: Personal Valuesmentioning
confidence: 99%